2015
DOI: 10.1111/tpj.13045
|View full text |Cite
|
Sign up to set email alerts
|

Embryo defective 14 encodes a plastid‐targeted cGTPase essential for embryogenesis in maize

Abstract: SUMMARYThe embryo defective (emb) mutants in maize genetically define a unique class of loci that is required for embryogenesis but not endosperm development, allowing dissection of two developmental processes of seed formation. Through characterization of the emb14 mutant, we report here that Emb14 gene encodes a circular permuted, YqeH class GTPase protein that likely functions in 30S ribosome formation in plastids. Loss of Emb14 function in the null mutant arrests embryogenesis at the early transition stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…S3 ). In these respects, duf177a has a typical maize emb phenotype as described in previous studies ( Clark and Sheridan, 1991 ; Ma and Dooner, 2004 ; Magnard et al , 2004 ; Sosso et al , 2012 ; Shen et al , 2013 ; Zhang et al , 2013 ; Li et al , 2015 ).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…S3 ). In these respects, duf177a has a typical maize emb phenotype as described in previous studies ( Clark and Sheridan, 1991 ; Ma and Dooner, 2004 ; Magnard et al , 2004 ; Sosso et al , 2012 ; Shen et al , 2013 ; Zhang et al , 2013 ; Li et al , 2015 ).…”
Section: Resultssupporting
confidence: 71%
“…These results indicated that duf177a mutant embryos do not progress beyond the early transition stage of embryogenesis. In this respect, the duf177a phenotype is similar to an emerging class of maize emb mutants implicated in disruption of plastid gene expression ( Ma and Dooner, 2004 ; Magnard et al , 2004 ; Sosso et al , 2012 ; Shen et al , 2013 ; Zhang et al , 2013 ; Li et al , 2015 ). In maize, the emb phenotypes of plastid gene expression mutants are suppressed in certain inbred backgrounds to condition an albino seedling phenotype ( Sosso et al , 2012 ; Zhang et al , 2013 ).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Notably, the Arabidopsis GCD ortholog has not been implicated in embryo patterning . In maize, a large class of mutants defective in plastid protein translation arrest embryogenesis at the transition stage (Magnard et al, 2004;Shen et al, 2013;Li et al, 2015;Yang et al, 2016) although it is not clear whether these genes have a direct role in controlling polarization of the embryo. Other investigations of patterning mechanisms during early embryogenesis in maize have largely relied on analysis of orthologs of Arabidopsis genes implicated in embryogenesis and polar auxin transport (Nardmann et al, 2007;Zimmermann and Werr, 2007;Chandler et al, 2008;Forestan et al, 2010;Chen et al, 2014).…”
Section: Shai1 Is Required For Proper Patterning and Organ Differentimentioning
confidence: 99%
“…On the other hand, many genes controlling maize kernel development have been cloned using kernel mutants identified from Robertson's Mutator stocks, including emp2 (empty pericarp2), emp4, emp5, emp16, dek1 (defective kernel1), dek35, maize pentatricopeptide repeat6, small kernel1, embryo defective14, U6 biogenesis-like1, and many others (Fu et al, 2002;Lid et al, 2002;Gutiérrez-Marcos et al, 2007;Manavski et al, 2012;Liu et al, 2013;Li et al, 2014Li et al, , 2015Chen et al, 2016;Xiu et al, 2016). Mutations in these genes usually have severe phenotypes in kernels, such as empty pericarp, where both embryo and endosperm cannot develop properly.…”
mentioning
confidence: 99%